Microfiber-Patterned Versatile Perfusable Vascular Networks - Ye Tian; Liqiu Wang (Micromachines, 2023)
Rapid construction of versatile perfusable vascular networks in vitro with cylindrical channels still remains challenging. Here, a microfiber-patterned method is developed to precisely fabricate versatile well-controlled perfusable vascular networks with cylindrical channels. This method uses tensile microfibers as an easy-removable template to rapidly generate cylindrical-channel chips with one-dimensional, two-dimensional, three-dimensional and multilayered structures, enabling the independent and precise control over the vascular geometry. These perfusable and cytocompatible chips have great potential to mimic vascular networks. The inner surfaces of a three-dimensional vascular network are lined with the human umbilical vein endothelial cells (HUVECs) to imitate the endothelialization of a human blood vessel. The results show that HUVECs attach well on the inner surface of channels and form endothelial tubular lumens with great cell viability. The simple, rapid and low-cost technique for versatile perfusable vascular networks offers plenty of promising opportunities for microfluidics, tissue engineering, clinical medicine and drug development.